Efforts toward the total synthesis of (±)-toxicodenane A utilizing an oxidopyrylium-based [5+2] cycloaddition of a silicon-tethered BOC-pyranone. Issue 38 (17th September 2020) - Grabowski, Jacob P.; Ferrence, Gregory M.; Mitchell, T. Andrew
Graphical abstract: Highlights: Synthetic efforts toward the tricyclic core of (±)-toxicodenane A are reported. Feist-Benary, Achmatowicz, Boc-protection used to construct precursor. Oxidopyrylium-based [5+2] cycloaddition of Boc-pyranone-vinyl silane. Abstract: Synthetic efforts toward the tricyclic core of (±)-toxicodenane A are reported. This strategy takes advantage of the Feist-Benary furan annulation, Achmatowicz oxidative rearrangement, and oxidopyrylium-based [5+2] cycloaddition to access a key tetracyclic intermediate. This work provides a foundation that can be utilized toward the total synthesis of the natural product.